2016
DOI: 10.17576/jkmjc-2016-3201-06
|View full text |Cite
|
Sign up to set email alerts
|

Keputusan Pembelian: Jalinan Antara Media Cetak, Media Atas Talian dan Media Bersemuka (Buying Decision: The Links Between Print Media, Online Media and Face-to-Face Media)

Abstract: AbstrakKeputusan pembelian pengguna terhadap suatu produk boleh dipengaruhi oleh pelbagai perkara seperti iklan, media dan faktor persekitaran. Dari perspektif media, keputusan pembelian pengguna tidak hanya bergantung kepada maklumat yang bersumberkan satu media sahaja. Sebaliknya, kecenderungan untuk mengurangkan risiko dalam pembelian akan mendorong pengguna untuk membina kefahaman yang lebih baik mengenai produk. Justeru, berteraskan kepada Teori Kekayaan Media, kajian ini bertujuan untuk mengenal pasti pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This finding is quite different from investigation carried out by (Idris et al, 2021) which found that the environment is a factor influencing on consumers' preferences to purchase halal beauty items, finding that is comparable to that of study from (Norman & Wahid, 2017), which they found that Environmental factors impact a consumer's choice of purchasing halal cosmetics. This is also supported by the findings of a study by (Mohamad et al, 2016) which states that advertising, media, and environmental factors influence consumer purchasing decisions.…”
Section: A the Effect Of Attitudes On Purchasing Decisionssupporting
confidence: 64%
“…This finding is quite different from investigation carried out by (Idris et al, 2021) which found that the environment is a factor influencing on consumers' preferences to purchase halal beauty items, finding that is comparable to that of study from (Norman & Wahid, 2017), which they found that Environmental factors impact a consumer's choice of purchasing halal cosmetics. This is also supported by the findings of a study by (Mohamad et al, 2016) which states that advertising, media, and environmental factors influence consumer purchasing decisions.…”
Section: A the Effect Of Attitudes On Purchasing Decisionssupporting
confidence: 64%
“…The issue of online fraud is one of the hot issues that is often debated by the public especially for those who are less fond of the world of digitization (Mohamad et al 2016). This online scam has also to some extent sparked a lack of trust in the purchase system.…”
Section: Scam Riskmentioning
confidence: 99%